Pengelolaan Bengkel Praktik Smk Teknik Pemesinan Di Kabupaten Purworejo - Purwanto Purwanto; Thomas Sukardi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2015)
This study aims to know the quality of: (1) planning, (2) organizing, (3) actuating, and (4) controlling of mechanical engineering workshop management at SMK in Purworejo Regency. This study is a quantitative study with survey method. The respondents of this study were the practical lesson teachers of mechanical engineering SMK in Purworejo Regency. The data collection techniques were questionnaire, interview, and observation. The data analysis technique used was descriptive statistics. The results showed that: (1) the planning has a good quality with a mean of 2.961; (2) the organizing has a good quality with a mean of 2.947; (3) the actuating has a good quality with a mean of 3.207; and (4) the controlling has a good quality with a mean of 2.874.